HARNESSING NATURE’S REMEDIES: A SYSTEMATIC REVIEW OF THE ANTIPYRETIC POTENTIAL OF INDONESIAN MEDICINAL PLANT EXTRACTS - Hardiana, Iyan; Wahyudin, Elly; Aswad, Muhammad; Agustina, Rina (Jurnal Farmasi Kryonaut, 2025)
Introduction: Fever is a common physiological response to infection and inflammation, typically managed with synthetic antipyretics like paracetamol and ibuprofen. However, concerns regarding their adverse effects have led to increased interest in natural alternatives. Indonesia, with its rich biodiversity, offers numerous medicinal plants with potential antipyretic properties. This systematic review evaluates the antipyretic efficacy of Indonesian medicinal plant extracts based on available clinical and preclinical studies. Methods: A systematic search was conducted in ScienceDirect, PubMed, Sage Journals, and Google Scholar following PRISMA guidelines. The review included randomized controlled trials (RCTs) and in vivo studies investigating the antipyretic effects of Indonesian medicinal plants compared to standard treatments or placebos. Study quality was assessed using the JADAD scale and ARRIVE checklist. Results: Nine eligible studies were analyzed, demonstrating that extracts from Cucumis sativus, Acalypha indica, Centella asiatica, and Castanopsis costata significantly reduced fever in animal models. These effects were attributed to bioactive compounds such as flavonoids, alkaloids, and saponins, which modulate prostaglandin synthesis and inflammatory pathways. Some extracts exhibited antipyretic efficacy comparable to conventional drugs, highlighting their therapeutic potential. Conclusion: Indonesian medicinal plants show promising antipyretic properties, suggesting their potential as alternative fever treatments. However, further clinical trials are required to confirm efficacy, optimize dosages, and ensure safety. Standardization of research methodologies and regulatory frameworks will be essential for their integration into modern healthcare